Comparitive Study On Multiplier Algorithms using Verilog HDL - MOHD SAPLI, NUR SY AHADAH (Universiti Teknologi Petronas, 2008)
Multipliers are used in many applications especially in computers. A personal computer (PC) utilizes multipliers to perform calculations. Thus, having a multiplier with great speed will definitely boost the performance of a PC. Based on this, the purpose of the Final Year Project is to perform a comparison study on multiplier algorithms using Verilog HDL. Four multipliers have been selected to be the subject of study. The multipliers are Ripple Carry multiplier, Carry Save multiplier, Wallace multiplier and finally the Dadda multiplier. The propagation delay of each multiplier is determined to check their performance in terms of speed. The outcome of this project has showed that, among these four multipliers, Carry Save multiplier has exhibited the smallest amount of propagation. Therefore, it is the fastest multiplier out of the four that are studied whereas Dadda multiplier shows the least number of logic elements used up until 6-bit multiplication process.